IMPLEMENTATION OF THE STUDENT COUNCIL PROGRAM IN IMPROVING STUDENTS' SENSE OF RESPONSIBILITY AND COOPERATION - Saragih, Ummi Aina; Lubis, M. Syukri Azwar; Harahap, Atika Hanan Julia (Yayasan Amanah Nur Aman, 2025)
This study examines how the implementation of the Student Council Program enhances students' sense of responsibility and cooperation at SMA Negeri 1 Bandar, Simalungun Regency. This research is a qualitative study with a natural observation research design. This study used research data collection techniques through observation, interviews, and documentation. Data validity was ensured through triangulation, and qualitative data analysis was used to analyze the data, which involved data reduction, presentation, and drawing conclusions. The findings of this study indicate that the planning of the Student Council program has been running well in accordance with the plan formulated through the Student Council work meeting. Student Council programs play an important role in shaping student character, particularly in terms of responsibility and cooperation. Further findings in this study indicate that the implementation of the Student Council (OSIS) program at this school is proceeding quite well. This is evident in the implementation of various OSIS activities planned through work meetings, then implemented in concrete activities such as national holiday commemorations, religious activities, inter-class competitions, community service, and other activities involving the entire school community. Despite obstacles in program implementation, the OSIS administrators demonstrated a fairly good sense of responsibility. Overall, however, the students' sense of responsibility is evident in their commitment to completing the planned work program. The results of the study indicate that the implementation of the OSIS program in enhancing students' sense of responsibility and cooperation at SMA Negeri 1 Bandar has been very effective in fostering a sense of responsibility and cooperation. Students who are active in OSIS activities show improvements in leadership aspects such as decision-making skills, responsibility, teamwork, communication skills, self-control, and motivation.